Electron Impact Excitation of Fe-like Tungsten Ion (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
Electron impact excitation of Fe-like tungsten ion has been studied using relativistic distorted wave theory. Cross-sections are obtained in the energy range upto 20 keV and their fitting is also provided for their potential application in plasma modeling. Polarization of the photon emission following the decay of the excited states is also analysed.
Keywords: Electron-impact excitation; Relativistic distorted wave; Polarization; tungsten ions